Evaluation of chitosan-Ag/TiO2 nanocomposite for the enhancement of shelf life of chili and banana fruits - Sourav Kumar Singha; Sheikh Manjura Hoque; Harinarayan Das; Md Abdul Alim (Heliyon, 2023)
Post-harvest losses of fruits and vegetables account for a large share of food waste in the world due to improper handling and packaging. By using the sol-gel method, Ag/TiO2 nanocomposite was prepared in this study from micro-sized commercial TiO2 powder and incorporated in a chitosan-cellulose matrix for the purpose of promising food packaging. The particle size and distribution of Ag nanoparticles (9.2437 nm size) confirmed their successful inclusion in the TiO2 surface. The morphology of the package assured the successful and uniform disbursement of Ag/TiO2 nanocomposite into the chitosan-cellulose matrix, which led to enhanced water resistance and photocatalytic activity. The developed package is proficient in hindering the growth of fecal coliform bacteria (Esche (Escherichia coli) by 9 mm in the agar plate. Moreover, the efficient application of chitosan-Ag/TiO2 nanocomposite in food coating and packaging was examined in extending shelf life, minimizing water loss, and preventing microbial infection during the storage of chili (up to 7 days at 37 °C) and banana, respectively. It can be concluded from the results that chitosan-Ag/TiO2 nanocomposite-based food coating and packaging have competent potential for enhancing the shelf life of moist foods.